1996
DOI: 10.1002/maco.19960471002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of graphite shape on the Corrosion of Grey Cast Iron in phosphoric acid

Abstract: Grey cast iron (3.4 %C-2.7 %Si-0.4 %Mn-0.05 %P-0.008 %S) with different morphology of graphite and different amount of ferrite, pearlite and eutectic phases has been subjected to corrosion and electrochemical tests in phosphoric acid solution, simulating the oxidized engine oil. The difference in the cathodic process and corrosion of studied materials has been mainly attributed to the variation of ferrite and pearlite volume fraction and to the presence of eutectic phases In the matrix of metals with different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…The test zone of the lamellar grey cast iron is completely worn by corrosion, Figure 15a The lamellar grey cast iron corroded severely, Figure 16. Because of a potential difference between the two phases, the less noble ferritic-pearlitic matrix in contact with the more noble carbon flakes corrodes preferentially, Figure 16b [40,25]. The carbon flakes lose stability in the matrix and dissolve into the medium.…”
Section: Metallographic Investigation After Potentiodynamic Polarizatmentioning
confidence: 99%
“…The test zone of the lamellar grey cast iron is completely worn by corrosion, Figure 15a The lamellar grey cast iron corroded severely, Figure 16. Because of a potential difference between the two phases, the less noble ferritic-pearlitic matrix in contact with the more noble carbon flakes corrodes preferentially, Figure 16b [40,25]. The carbon flakes lose stability in the matrix and dissolve into the medium.…”
Section: Metallographic Investigation After Potentiodynamic Polarizatmentioning
confidence: 99%
“…E-mail: kassiazzoug@gmail.com Overseas Foundry are in relation to the nucleation process and morphological transformations of graphite. The latter is dependent on the tensile strength of the cast iron (cracking sites) and the corrosion behavior in some corrosive environments [7,10,[19][20][21][22] .…”
Section: *M O Azzougmentioning
confidence: 99%
“…Lunarska [7] studied the effect of the graphite form on corrosion of gray cast iron in acid phosphoric (H 3 PO 4 ). He concluded that the vermicular form of graphite is beneficial to the mechanical and tribological properties.…”
Section: *M O Azzougmentioning
confidence: 99%
See 2 more Smart Citations